Control of Dendritic Arborization by the Phosphoinositide-3′-Kinase–Akt–Mammalian Target of Rapamycin Pathway - Jaworski, Jacek (J Neurosci, 2005)
The molecular mechanisms that determine the size and complexity of the neuronal dendritic tree are unclear. Here, we show that the phosphoinositide-3′ kinase (PI3K)–Akt–mammalian target of rapamycin (mTOR) signaling pathway promotes the growth and branching of dendrites in cultured hippocampal neurons. Constitutively active mutants of Ras, PI3K, and Akt, or RNA interference (RNAi) knockdown of lipid phosphatase PTEN (phosphatase and tensin homolog deleted on chromosome Ten), induced growth and elaboration of dendrites that was blocked by mTOR inhibitor rapamycin and/or by overexpression of eIF-4E binding protein 1 (4E-BP1), which inhibits translation of 5′ capped mRNAs. The effect of PI3K on dendrites was lost in more mature neurons (>14 d in vitro). Dendritic complexity was reduced by inhibition of PI3K and by RNAi knockdown of mTOR or p70 ribosomal S6 kinase (p70S6K, an effector of mTOR). A rapamycin-resistant mutant of mTOR “rescued” the morphogenetic effects of PI3K in the presence of rapamycin. By regulating global and/or local protein translation, and as a convergence point for multiple signaling pathways, mTOR could play a central role in the control of dendrite growth and branching during development and in response to activity.